Preparation method of magnesium carbonate trihydrate pellets as cement early strength agent
By making magnesium carbonate trihydrate into spherical particles and forming thin-layer phases on its surface, the problem of low incorporation of magnesium carbonate trihydrate in cement and slow hydration reaction process is solved, and the early strength of cement and the efficiency of hydration reaction is significantly improved.
Patent Information
- Application Number
- CN202411950090.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The prior art has problems such as high cost, high safety hazards and slow hydration reaction when curing cement concrete using carbon dioxide atmosphere. The amount of magnesium carbonate trihydrate in cement is relatively low, which affects the early strength development.
By making magnesium carbonate trihydrate into spherical particles and forming thin layers of matter on its surface, nearly spherical secondary particles with a certain strength are formed, flash condensation caused by rapid dissolution, and uniformly dispersed in cement to promote hydration reaction.
The high amount of magnesium carbonate trihydrate in cement is achieved, which avoids rapid condensation, promotes the development of early strength of cement, and improves the efficiency of hydration reaction.
Smart Images

Figure CN119898981A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based material preparation, in particular to a method for preparing magnesium carbonate trihydrate pellets used as a cement early strength agent. Background Art
[0002] Carbon dioxide gas is a byproduct of the production process of Portland cement and is also a greenhouse gas. About 1 ton of carbon dioxide is released for every ton of cement clinker produced. At present, carbon dioxide gas has been used in the production of cement prefabricated components or products in factories, and it is also an effective way to recycle carbon dioxide. Carbon dioxide gas will promote the hydration of Portland cement. Not only will the clinker mineral C3S accelerate hydration under the action of carbon dioxide, but C2S also has a similar phenomenon of promoting hydration. As a result, the early strength of cement is significantly improved, which is very beneficial to the strength development of road cement concrete. However, there are many difficulties in using carbon dioxide atmosphere to maintain cement concrete in road projects. Not only does it increase the maintenance cost, but there are also safety hazards that are easily caused by the use of carbon dioxide gas cylinders. In addition, the carbonation of carbon dioxide promotes the maintenance process, which is a reaction process that gradually penetrates deep into the concrete from the surface of the concrete, so the process is relatively slow.
[0003] According to the applicant's previous research, carbon dioxide gas was solidified in the crystal structure of magnesium carbonate trihydrate (MgCO3·3H2O), that is, magnesium carbonate trihydrate was used as a solid carrier of carbon dioxide. It was found that magnesium carbonate trihydrate has an accelerating effect on the early strength of silicate cement. A small amount of magnesium carbonate trihydrate can shorten the final setting time of the benchmark cement to less than 10 minutes. The invention patent CN110981257B "An alkali-free and chlorine-free concrete accelerator based on magnesium carbonate trihydrate" is to apply magnesium carbonate trihydrate to concrete accelerators. Magnesium carbonate trihydrate dissolves in cement alkaline solution and releases CO3 2- When magnesium carbonate trihydrate is mixed evenly with cement powder and water is added, CO3 will soon appear everywhere in the slurry inside the cement mixture. 2- The ion concentration increases rapidly. When the addition amount of magnesium carbonate trihydrate is 1%, a significant accelerating effect can be obtained. When the addition amount exceeds 3%, flash setting occurs and the cement paste quickly loses its working performance.
[0004] In order to increase the dosage of magnesium carbonate trihydrate, avoid too fast coagulation, introduce more carbon dioxide components, and promote cement hydration, the applicant treated the surface of magnesium carbonate trihydrate and prepared it into spherical secondary particles of magnesium carbonate trihydrate. The study found that adding magnesium carbonate trihydrate pellets to silicate cement does not cause the cement to coagulate quickly, thus not affecting the working performance of the cement paste. After pouring, the magnesium carbonate trihydrate pellets release CO3 into the cement slurry. 2- ions can achieve the purpose of promoting cement hydration. Summary of the invention
[0005] The present invention provides a method for preparing magnesium carbonate trihydrate pellets as a cement early strength agent. A thin layer of phase is generated on the surface of magnesium carbonate trihydrate crystals through an in-situ reaction. The phase not only combines the magnesium carbonate trihydrate particles into nearly spherical secondary particles with a certain strength, but also inhibits the flash coagulation phenomenon caused by the rapid dissolution of magnesium carbonate trihydrate in cement slurry. When the magnesium carbonate trihydrate pellets are mixed with cement slurry, they are evenly dispersed in the cement slurry and do not affect the working performance of the slurry. When magnesium carbonate trihydrate begins to dissolve in the cement slurry, Mg is released. 2+ and CO3 2- ions, causing Ca 2+ The concentration and pH value decrease, and this process promotes the hydration of cement clinker minerals C3S and C2S.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] The present invention provides a method for preparing magnesium carbonate trihydrate pellets as a cement early strength agent, comprising preparing magnesium carbonate trihydrate pellets and then generating a thin layer of phase on the surface of the pellets. The specific steps are as follows:
[0008] S1. Place magnesium carbonate trihydrate powder and water or alkaline solution in a blender, mix and then roll, and filter out excess water;
[0009] S2, placing the rolled material in a disc granulator to obtain nearly spherical particles;
[0010] S3, curing the nearly spherical particles under a sealed condition, and after curing, a thin layer of phase with basic magnesium carbonate as the main component is formed on the surface of the magnesium carbonate trihydrate crystals;
[0011] S4. The particles obtained by curing are dried and sieved to obtain magnesium carbonate trihydrate pellets.
[0012] Preferably, in step S1, the magnesium carbonate trihydrate may be a columnar magnesium carbonate trihydrate crystal obtained by reacting a suspension of magnesium chloride, magnesium oxide or magnesium hydroxide with water with CO2 at a temperature of 15°C to 40°C and normal pressure, or may be a columnar magnesium carbonate trihydrate crystal obtained by reacting a soluble carbonate such as ammonium carbonate, sodium carbonate, potassium carbonate with a soluble magnesium salt such as magnesium sulfate, magnesium chloride, etc. at a temperature of 15°C to 40°C and normal pressure. The magnesium carbonate trihydrate powder is the columnar magnesium carbonate trihydrate crystal prepared above and its crushed product.
[0013] Preferably, in step S1, the water is ordinary drinking water, distilled water or deionized water; the alkaline solution is one of a saturated or unsaturated solution of magnesium hydroxide, a saturated or unsaturated solution of calcium hydroxide, and a filtrate with a pH value of ≥10 obtained by reacting silicate cement with water.
[0014] Preferably, in step S1, the mass ratio of magnesium carbonate trihydrate powder to water or alkaline solution is 1:(0.2~1.0).
[0015] Preferably, in step S1, after the magnesium carbonate trihydrate powder is mixed with water or an alkaline solution, it is first stirred at a speed of 50-200 rpm for 0.5-5 min, and then stirred at a speed of 500-2000 rpm for 0.5-2 min, and the rolling pressure is 5-20 MPa.
[0016] Preferably, in step S2, the rotation speed of the disc granulator is 600-800 rpm, and after granulation, nearly spherical particles with a particle size of φ0.18-2.36 mm are screened, and particles with a particle size not within this range are returned to the granulator for granulation.
[0017] Preferably, in step S3, if the added medium is water, the curing conditions are wet heat curing at 60-80°C for 10 min to 2 d under sealed conditions; if the added medium is an alkaline solution, the curing conditions are curing at 20-80°C for 10 min to 7 d under sealed conditions.
[0018] Preferably, in step S3, the phases generated on the surface of the magnesium carbonate trihydrate crystals are mainly calcite, hydromagnesite, fibrous hydromagnesite, etc., all of which belong to basic magnesium carbonate, and the mass percentage of the above phases in the magnesium carbonate trihydrate pellets is ≤1.0%.
[0019] Preferably, in step S4, the drying temperature is 50-60° C., and the dried particles are sieved through 80 mesh, 32 mesh, 16 mesh and 8 mesh screens to form magnesium carbonate trihydrate spheres in three particle size ranges of 0.18-0.50, 0.50-1.00 and 1.00-2.36 mm. The above three particle size ranges correspond to the early strength development requirements at different ages.
[0020] The invention also provides magnesium carbonate trihydrate pellets prepared by the method.
[0021] The present invention also provides the use of the magnesium carbonate trihydrate pellets as a cement early strength agent. After the magnesium carbonate trihydrate is made into pellets and a thin layer of phase is formed on the surface, the amount of the magnesium carbonate trihydrate added into cement can be ≥5% (by mass).
[0022] The beneficial effects of the technical solution of the present invention are as follows:
[0023] The present invention adopts magnesium carbonate trihydrate, a carbon-fixing product of magnesium, as a solid carrier of carbon dioxide, which overcomes many difficulties in curing cement concrete in a carbon dioxide atmosphere, and also solves the problem of low addition of magnesium carbonate trihydrate in cement. Since magnesium carbonate trihydrate pellets have good dispersibility in cement paste, the hydration reaction process is accelerated at all places inside the cement paste, inducing crystallization of hydration products, and greatly promoting the early strength development of cement.
[0024] In particular, the rotation speed in step S1 is changed from slow to fast, so that the solution and magnesium carbonate trihydrate can be fully mixed, and different mediums should be mixed with magnesium carbonate trihydrate at different rotation speeds, so that the needle-shaped crystals of magnesium carbonate trihydrate can be more resilient after stirring. Under different pressure conditions in step S1, step S2 is used to produce more closely combined magnesium carbonate trihydrate pellets through a disc granulator. Finally, in step S3, the type and quantity of thin layer phases generated on the surface of magnesium carbonate trihydrate pellets are controlled by curing temperature and curing time. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 This is a photo of magnesium carbonate trihydrate pellets prepared in Example 1 of the present invention.
[0027] Figure 2 This is the SEM morphology of the crystals inside the magnesium carbonate trihydrate spherules of Example 1 of the present invention.
[0028] Figure 3 This is a phase analysis of the composition of the magnesium carbonate trihydrate pellets of the present invention. DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0030] The present invention provides a method for preparing magnesium carbonate trihydrate pellets as a cement early strength agent. A thin layer of phase is generated on the surface of magnesium carbonate trihydrate crystals through an in-situ reaction. The phase not only combines magnesium carbonate trihydrate particles into nearly spherical secondary particles with a certain strength, but also inhibits the flash coagulation phenomenon caused by the rapid dissolution of magnesium carbonate trihydrate in cement slurry. The magnesium carbonate trihydrate pellets are added to cement, which does not cause the cement to coagulate rapidly and does not affect the working performance of the cement slurry. After pouring, the magnesium carbonate trihydrate pellets release CO3 into the cement slurry. 2-Ions can promote cement hydration.
[0031] Magnesium carbonate trihydrate is a magnesium-based carbon-fixing product that can be formed at room temperature and pressure. It can be obtained by reacting magnesium salts, magnesium oxide, and magnesium hydroxide directly with carbon dioxide, or indirectly through the reaction of soluble carbonates. Magnesium carbonate trihydrate crystals are columnar and can be used directly or after being crushed.
[0032] Magnesium carbonate trihydrate powder and water or alkaline solution with a mass of 0.2~1.0 times its mass are placed in a blender. This mass ratio can theoretically generate the maximum amount of basic magnesium carbonate. First, slowly mix and stir at a speed of 50rpm~200rpm for 0.5 min~5min, and then quickly stir at a speed of 500rpm~2000rpm for 0.5min~2min. The smaller the ratio of water or solution medium to magnesium carbonate trihydrate, the smaller the blender mixing speed. Depending on the ratio of the medium, the mixture is in three states: granular, lumpy and paste. The mixture is rolled under a roller, and the rolling pressure is adjustable at 5MPa~20MPa. The granular mixture can be aggregated into larger granules after rolling. The paste mixture has liquid exudate after rolling, and the exudate needs to be filtered out. After rolling, the magnesium carbonate trihydrate in the mixture is more densely distributed. After the rolled material is beaten into small particles on a granulator, it is granulated by rotation to obtain nearly spherical composite particles.
[0033] The water mentioned above is ordinary drinking water, distilled water, deionized water, etc., and the alkaline solution is a solution with a pH value of not less than 10, such as a saturated or unsaturated solution of magnesium hydroxide, a saturated or unsaturated solution of calcium hydroxide, and a filtrate of the reaction of silicate cement with water. The silicate cement includes PI, PII type silicate cement, PO ordinary silicate cement, PS slag silicate cement, PF fly ash silicate cement, PP pozzolana silicate cement and PC composite silicate cement, as well as PR road silicate cement, etc. The filtrate of the reaction of silicate cement with water is a slurry filtrate of cement reacting with water with a mass of more than 10 times that of cement for more than 2 hours.
[0034] The above particles with water as the medium are cured at 60°C to 80°C for 10min to 2d under sealed conditions. The higher the temperature, the shorter the curing time. When the temperature exceeds 70°C, the curing time is controlled to be less than 30min. The particles with alkaline solution as the medium are cured at 20°C to 80°C for 10min to 7d under sealed conditions. When the temperature exceeds 70°C, the curing time is controlled to be less than 30min. The present invention selects different curing conditions according to different media to generate basic magnesium carbonate on the surface of magnesium carbonate trihydrate, thereby obtaining spherical particles.
[0035] When water is used as the medium, due to kinetic factors, magnesium carbonate trihydrate will only transform into fullerene [4MgCO3·Mg(OH)2·5H2O] and hydromagnesite [4MgCO3·Mg(OH)2·4H2O] according to the reactions shown in equations (1) and (2) after wet heat curing at a temperature above 60°C. These two reactions accelerate after 70°C, and as the curing temperature increases, hydromagnesite is more likely to be generated.
[0036] 5 (MgCO3·3H2O) → 4MgCO3·Mg(OH)2·5H2O + CO2+9 H2O (1)
[0037] 5 (MgCO3·3H2O) → 4MgCO3·Mg(OH)2·4H2O + CO2+10 H2O (2)
[0038] When Mg(OH)2 solution is used as the medium, the phase of magnesium carbonate trihydrate changes according to equations (3) and (4). These two reactions can be carried out at room temperature and are accelerated as the temperature rises.
[0039] 4 (MgCO3·3H2O) + Mg(OH)2 → 4MgCO3·Mg(OH)2·5H2O +7 H2O (3)
[0040] 4 (MgCO3·3H2O) + Mg(OH)2 → 4MgCO3·Mg(OH)2·4H2O + 8 H2O (4)
[0041] When Ca(OH)2 solution (including cement hydration slurry) is used as the medium, the transformation of magnesium carbonate trihydrate is carried out according to equations (5) and (6). These two reactions can be carried out at room temperature, and the reaction is accelerated as the temperature rises.
[0042] 5 (MgCO3·3H2O) + Ca(OH)2 → 4MgCO3·Mg(OH)2·5H2O + CaCO3 + 10 H2O (5)
[0043] 5 (MgCO3·3H2O) + Ca(OH)2 → 4MgCO3·Mg(OH)2·4H2O + CaCO3 + 11 H2O (6)
[0044] From the above process, it can be seen that when water is used as the medium, the reaction process of magnesium carbonate trihydrate being converted into basic magnesium carbonate will release CO2. When alkaline solution is used as the medium, the reaction will not release CO2, which is more environmentally friendly.
[0045] The cured particles are dried in a drying oven at a temperature not exceeding 60° C. for 24 hours, and the dried particles are sieved through 80-mesh, 32-mesh, 16-mesh and 8-mesh sieves to form magnesium carbonate trihydrate granules in three particle size ranges of 0.18-0.50, 0.50-1.00 and 1.00-2.36 mm.
[0046] The present invention generates a thin layer of phase on the surface of magnesium carbonate trihydrate crystals through an in-situ reaction. The higher the curing temperature, the less time it takes to generate the thin layer of phase. When the mixed medium is an alkaline solution, even if the curing temperature is low, a thin layer of phase can be generated if the curing time is long enough. The alkaline solution combines with the magnesium carbonate trihydrate particles to form nearly spherical secondary particles with a certain strength, and can also inhibit the flash coagulation phenomenon caused by the rapid dissolution of magnesium carbonate trihydrate in cement slurry. When the magnesium carbonate trihydrate granules are mixed with cement slurry, they are evenly dispersed in the cement slurry and do not affect the working performance of the slurry. When magnesium carbonate trihydrate begins to dissolve in the cement slurry, Mg is released. 2+ and CO3 2- ions, causing Ca 2+ The concentration and pH value decrease, and this process promotes the hydration of cement clinker minerals C3S and C2S. Magnesium carbonate trihydrate is used as a solid carrier of CO2 in cement-based materials, which has the effect of inducing cement hydration and promoting the early strength development of cement.
[0047] This will be described below with reference to specific embodiments.
[0048] Example 1
[0049] Magnesium carbonate trihydrate powder and 0.3 times its mass of water are placed in a mixer, first slowly mixed and stirred at 100rpm for 1min, and then quickly stirred at 1000rpm for 1min. Take the evenly mixed material out of the mixer, put it under a roller and roll it clockwise for 5 times at 5MPa, and then roll it counterclockwise for 5 times. The rolled material is placed in a disc granulator, and the speed is adjusted to 700rpm. When the pellets are prepared, use a sieve to screen out nearly spherical particles with a particle size of φ0.18~2.36mm, and return the particles outside this range to the granulator for granulation. The above particles are wet-heat cured at 60℃ for 48h under sealed conditions. After wet-heat curing, dry them in a drying oven at 60℃ for 24h and cool to room temperature to obtain magnesium carbonate trihydrate pellets with good strength. The parameters are shown in Table 1.
[0050] The morphology of the spherical magnesium carbonate trihydrate particles prepared in this example is as follows Figure 1 As shown, after testing, the particle size range is φ0.18~2.36mm, with good sphericity and high strength; Figure 2The morphology of magnesium carbonate trihydrate particles inside the pellet after curing shows that magnesium carbonate trihydrate is a needle-shaped crystal with a flat surface. When basic magnesium carbonate flake crystals are generated on the surface, the surface morphology of the crystal changes. The thickness of the thin layer formed on the surface of magnesium carbonate trihydrate particles is less than 100nm. The characteristic peak of basic magnesium carbonate appears in the XRD diagram, while the original magnesium carbonate trihydrate does not have this peak, which proves that basic magnesium carbonate is generated.
[0051] Figure 3 The phase analysis of the magnesium carbonate trihydrate pellets of the present invention is as follows: # is the XRD spectrum of magnesium carbonate trihydrate raw material, 2 # The XRD spectrum of the product of Example 1 shows that the surface phase of the pellet is mainly basic magnesium carbonate, and the interior is still magnesium carbonate trihydrate. Furthermore, the thin layer of the surface phase of magnesium carbonate trihydrate crystal is fullerite. Combined with the results of thermogravimetric analysis, it can be seen that the fullerite content is less than 1%, and the density of the pellet is about 1.0g / cm 3 .
[0052] When PO 42.5 ordinary Portland cement is used and the addition amount of magnesium carbonate trihydrate pellets is 5% of the cement mass, the fluidity of the mortar mixture is normal, and the compressive strength of the mortar samples at 1d and 3d is increased by 26.4% and 21.5% respectively compared with the case without addition.
[0053] Example 2
[0054] The other conditions are the same as those in Example 1, except that the medium mixed with magnesium carbonate trihydrate is a saturated solution of magnesium hydroxide, as shown in Table 1. The spherical particles of magnesium carbonate trihydrate prepared in this example have good sphericity and high strength after testing; the surface product phase is fullerene with a content of less than 1% and a bulk density of about 1.2 g / cm 3 .
[0055] When PO 42.5 ordinary Portland cement is used and the addition amount of magnesium carbonate trihydrate pellets is 10% of the cement mass, the fluidity of the mortar mixture is normal, and the compressive strength of the mortar samples at 1d and 3d is increased by 33.2% and 28.0% respectively compared with the case without addition.
[0056] Example 3
[0057] Other conditions are the same as those in Example 1, except that the medium mixed with magnesium carbonate trihydrate is the slurry filtrate obtained by reacting P.O42.5 cement with 10 times water for 6 hours, with a pH value of 12.67, and the amount added is 0.3 times the mass of magnesium carbonate trihydrate powder. When mixing, first slowly mix and stir at 80rpm for 2 minutes, and then quickly stir at 800rpm for 0.5 minutes. The rolling pressure is adjusted to 5MPa, and the curing temperature is reduced from 60°C to 40°C, as shown in Table 1. The spherical particles of magnesium carbonate trihydrate prepared in this embodiment have good sphericity and high strength after testing; the surface product phase is mainly calcite, and a small amount of calcite is also found, the total content of the two is less than 1%, and the density of the particles is about 0.9g / cm 3 .
[0058] When PO 42.5 ordinary Portland cement is used and the addition amount of magnesium carbonate trihydrate pellets is 8% of the cement mass, the fluidity of the mortar mixture is normal, and the compressive strength of the mortar samples at 1d and 3d are increased by 28.3% and 30.5% respectively compared with the case without addition.
[0059] Comparative Example 1
[0060] The other conditions are the same as those in Example 1, except that the wet heat curing temperature is 100°C and the curing time is 0.5h. The spherical particles prepared in this comparative example are tested to have good sphericity and high strength; Figure 3 Middle 3 # The XRD spectrum of the product of Comparative Example 1 shows that a large amount of calcite and hydromagnesite are generated, with the content of the two accounting for more than 70%, and the residual magnesium carbonate trihydrate is less than 30%. The prepared pellets are not magnesium carbonate trihydrate pellets, and the pellet density is about 0.6g / cm 3 .
[0061] When PO 42.5 ordinary Portland cement is used and the amount of magnesium carbonate trihydrate pellets added is 5% of the cement mass, the fluidity of the mortar mixture is normal, but the compressive strength of the mortar samples at 1d and 3d is only increased by 0.5% and 2.1% respectively compared with the case without addition. This indicates that the curing temperature is too high and the main phase of the pellets is not magnesium carbonate trihydrate, so the strength cannot be improved.
[0062] Comparative Example 2
[0063] The other conditions are the same as those in Example 2, except that the rolling pressure is changed to 0.5 MPa. The magnesium carbonate trihydrate particles prepared in this comparative example are tested to have poor sphericity and low strength; the thin layer phase on the surface of the magnesium carbonate trihydrate crystal is fullerene, the thin layer phase content is less than 1%, and the particle density is about 0.6 g / cm 3 .
[0064] When the amount of magnesium carbonate trihydrate pellets added was 5% of the cement mass, the pellets broke during the mixing process due to the low rolling pressure, the fluidity of the mortar mixture became poor, and the casting was difficult. The compressive strength of the mortar samples at 1d and 3d was only increased by 1.5% and 6.4% respectively compared with the case without addition.
[0065] Table 1 Comparison between the embodiments of the present invention and the comparative examples
[0066]
[0067] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing magnesium carbonate trihydrate pellets as a cement early strength agent, characterized in that: The steps include: S1. Place magnesium carbonate trihydrate powder and water or alkaline solution in a blender, mix and then roll, and filter out excess water; S2, placing the rolled material in a disc granulator to obtain nearly spherical particles; S3, curing the nearly spherical particles under a sealed condition; S4. The particles obtained by curing are dried and sieved to obtain magnesium carbonate trihydrate pellets.
2. The method for preparing magnesium carbonate trihydrate pellets as a cement early strength agent according to claim 1, characterized in that: In step S1, the magnesium carbonate trihydrate is reacted by a suspension of magnesium chloride, magnesium oxide or magnesium hydroxide and water with CO2 at a temperature of 15°C to 40°C and normal pressure to obtain columnar magnesium carbonate trihydrate crystals; or by a soluble carbonate and a soluble magnesium salt reacting at a temperature of 15°C to 40°C and normal pressure to obtain columnar magnesium carbonate trihydrate crystals.
3. The method for preparing magnesium carbonate trihydrate pellets as a cement early strength agent according to claim 2, characterized in that: In step S1, the water is drinking water, distilled water or deionized water; the alkaline solution is one of a saturated or unsaturated solution of magnesium hydroxide, a saturated or unsaturated solution of calcium hydroxide, and a filtrate with a pH value of ≥10 obtained by reacting silicate cement with water.
4. The method for preparing magnesium carbonate trihydrate pellets as a cement early strength agent according to claim 3, characterized in that: In step S1, the mass ratio of magnesium carbonate trihydrate powder to water or alkaline solution is 1:(0.2-1.0).
5. The method for preparing magnesium carbonate trihydrate pellets as a cement early strength agent according to claim 4, characterized in that: In step S1, after the magnesium carbonate trihydrate powder is mixed with water or an alkaline solution, it is first stirred at a speed of 50-200 rpm for 0.5-5 min, and then stirred at a speed of 500-2000 rpm for 0.5-2 min, and the rolling pressure is 5-20 MPa.
6. The method for preparing magnesium carbonate trihydrate pellets as a cement early strength agent according to claim 1, characterized in that: In step S2, the rotation speed of the disc granulator is 600-800 rpm, and after granulation, nearly spherical particles with a particle size of φ0.18-2.36 mm are sieved.
7. The method for preparing magnesium carbonate trihydrate pellets as a cement early strength agent according to claim 1, characterized in that: In step S3, if the added medium is water, the curing condition is wet heat curing at 60-80°C for 10 min to 2 d under sealed conditions; if the added medium is an alkaline solution, the curing condition is curing at 20-80°C for 10 min to 7 d under sealed conditions.
8. The method for preparing magnesium carbonate trihydrate pellets as a cement early strength agent according to claim 1, characterized in that: In step S3, the physical phase generated on the surface of the magnesium carbonate trihydrate crystals after curing is basic magnesium carbonate, and the mass percentage of basic magnesium carbonate in the magnesium carbonate trihydrate pellets is ≤1.0%.
9. Magnesium carbonate trihydrate pellets prepared by the method according to any one of claims 1 to 8.
10. The use of the magnesium carbonate trihydrate pellets according to claim 9 as a cement early strength agent, characterized in that: The amount of magnesium carbonate trihydrate pellets added to cement is ≥5%.
Citation Information
Patent Citations
Binder composition
CN102083764A
Binder composition
CN103153908A
Enhanced reactive magnesia cement-based concrete mixes
CN110446685A
Alkali-free and chlorine-free concrete accelerator based on magnesium carbonate trihydrate
CN110981257A
Porous material taking magnesium carbon sequestration product as raw material and preparation method thereof
CN113264751A